PERTUMBUHAN DAN PRODUKSI JAGUNG (Zea mays L. ) DAN KACANG TANAH (Arachis hypogaea L.) MELALUI PEMBERIAN NUTRISI ORGANIK DAN WAKTU TANAM DALAM SISTEM TUMPANGSARI - Arma, Makmur Jaya; Fermin, Uli; Sabaruddin, Laode (Jurnal Agroteknos, 2013)
The aims of this research were to understand the effects of organic nutrients and planting time in intercropping system on growth and yield the maize (Zea mays L.) and peanut (Arachis hypogaea L.). The research was conducted at Experimental Farm and Laboratory of the Faculty of Agriculture, University of Haluoleo Kendari, on July to October 2012. The experiment was arranged in Completely Randomized Block Design (CRBD) in a the split plot design, which consisted of dosage of organic nutrients (S) as main plot, with three levels, S0 without organic nutrients, S1 dose 1 mL L-1 water of organic nutrients and S2 dose 2 mL L-1 water of organic nutrients. Planting time (W) as sub plot, consisted of three levels, W0 = planting time of peanut together with maize, W1= planting time of peanut 10 day before maize and W2 = planting time of peanut 10 day after maize. Combination of treatment was repeated three times. Data obtained were analyzed using analysis of variance and followed by Duncan’s Multiple Range Test. The results showed that the highest maize productivity was 7.31 ton ha-1 and peanuts 2.21 ton ha-1 obtained of the treatment of growth hormone dose of 1 mL L-1 and peanut cultivation 10 day before maize. Treatment of 1 mL L-1 water of organic nutrients and planting time of peanut 10 day before maize can improve growth and yield of maize and peanut crops and thus can be a recommendation in intercropping systems on maize and peanut. Keywords: maize, peanut, growth hormone, planting time in intercropping system